2018
DOI: 10.3390/ijms19020482
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Dynamics and the Evolution of Cancer Genome Architecture

Abstract: Telomeres are progressively eroded during repeated rounds of cell division due to the end replication problem but also undergo additional more substantial stochastic shortening events. In most cases, shortened telomeres induce a cell-cycle arrest or trigger apoptosis, although for those cells that bypass such signals during tumour progression, a critical length threshold is reached at which telomere dysfunction may ensue. Dysfunction of the telomere nucleoprotein complex can expose free chromosome ends to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 143 publications
1
30
0
Order By: Relevance
“…While telomere maintenance is complex as well as essential for cancer progression (78), deficient telomerase activity and telomere shortening have been both reported in SSc (79, 80). In another fibrotic condition, IPF, telomere shortening is also a potential contributor for the pathological process and reduction in telomere length of circulating leukocytes could even have an impact on overall mortality (81).…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…While telomere maintenance is complex as well as essential for cancer progression (78), deficient telomerase activity and telomere shortening have been both reported in SSc (79, 80). In another fibrotic condition, IPF, telomere shortening is also a potential contributor for the pathological process and reduction in telomere length of circulating leukocytes could even have an impact on overall mortality (81).…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…Its discovery in the 1980s was recognized by the reception of the 2009 Nobel Prize in Physiology of Medicine [ 45 , 46 , 47 , 48 ]. Telomerase activity was found to be higher in germline and stem cells and nearly absent in somatic cells, which explains the normally occurring telomeric shortening with each cell division [ 49 , 50 ]. In 1997, telomerase activity in cHL was detected for the first time by Brousset et al [ 51 ] and Bryan et al described the principle of alternative lengthening of telomeres (ALT), a telomerase-independent pathway able to maintain telomeric length in malignant tumors [ 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…Relevant and important processes occur in normal and pathological tissues, including malignant tumors, and more than 50 reviews have been published in 2018 alone on these issues (for example, [14,15,16]). It is believed that several peculiarities (dysregulation) in the functioning and dynamics of telomeres exist in human malignant cells (HMCs) that are not present in normal cells [1,7,17,18,19]. Moreover, it has been shown that telomerase activity is either not defined or is detectable at low levels in normal cells [20,21,22].…”
Section: Introductionmentioning
confidence: 99%